The Risk Pivot Great Powers, International Security, and the Energy Revolution - Jones, Bruce D. (Brookings Institution Press, 2014)
The last decade has seen a revolution in global energy. First, we saw explosive growth in demand from Asia's rising powers, which fueled fears about scarcity and conflict. But we've also seen an American revolution in technology and markets, resulting in a dramatic increase in sup-ply. This is strengthening America's hand in the world-but it's not without complications. There are major security consequences of these shifts. Among the most consequential are China and India, Asia's emerging giants, which are increasingly exposed to political risks associated with energy risks, as well as the energy flows, pivoting to Asia. Meanwhile the great powers struggle to balance their need for fossil fuels with a mounting effort to tackle climate change. The top powers, and the United States above all, face a stra-tegic choice: whether to use energy as a weapon of geopolitics, or as a tool of a stable order.CONTENTS Introduction1. The President and the King-Key Messages of the Book2. The Energy Revolutions-A PrimerGeopolitics in Flux-The Players3. Choices-Scenarios, and the Choice the Powers Confront4. Rough Seas Ahead-The Great Powers' Search for Energy SecurityGlobalization and Complexity-The Problems5. Transition in the Gulf6. The Turbulent Middle7. Fragile States8. The Russian Problem9. Connections-from Pipelines to PoliticsGovernance-The Partners10. An Emerging System of Global Energy Governance11. Leadership Choices
Description based on publisher supplied metadata and other sources
Keywords: Energy consumption; Energieversorgung; Sicherheitspolitik; Großmacht